Dose-dependent effect of GFI1 expression in the reconstitution and the differentiation capacity of HSCs - Xie, Xiaoqing; Patnana, Pradeep Kumar; Frank, Daria; Schütte, Judith; Al-Matary, Yahya; Künstner, Axel; Busch, Hauke; Ahmed, Helal; Liu, Longlong; Engel, Daniel R.; Dührsen, Ulrich; Rosenbauer, Frank; et al. (Frontiers in Cell and Developmental Biology, 2023)
GFI1 is a transcriptional repressor and plays a pivotal role in regulating the differentiation of hematopoietic stem cells (HSCs) towards myeloid and lymphoid cells. Serial transplantation of Gfi1 deficient HSCs repopulated whole hematopoietic system but in a competitive setting involving wild-type HSCs, they lose this ability. The underlying mechanisms to this end are poorly understood. To understand this, we used mouse strains that express either loss of both Gfi1 alleles (Gfi1-KO), reduced expression of GFI1 (GFI1-KD) or wild-type Gfi1/GFI1 (Gfi1-/GFI1-WT; corresponding to the mouse and human alleles). We observed a 2-4 fold fewer HSCs in GFI1-KD/-KO compared to GFI1-WT mice. To investigate GFI1 expression levels on HSCs function, sorted HSCs from Gfi1-WT (CD45.1+) and GFI1-KD/-KO (CD45.2+) mice were co-transplanted into lethally irradiated host mice. Every four weeks, CD45.1 and CD45.2 expression on different lineage mature cells were analyzed. Sixteen weeks later, mice were analysed for the expression of CD45.1 and CD45.2 on HSCs, GMPs, CMPs and MEPs in the total bone marrow cells. In the case of co-transplantation of GFI1-KD with Gfi1-WT HSCs, the majority of HSCs (81% ± 6 %) and mature cells (88% ± 10%) originated from CD45.2+ GFI1-KD HSCs. Whereas, co-transplantation of Gfi1-KO HSCs with Gfi1-WT HSCs, the majority of HSCs originated from CD45.2+ and therefore from Gfi1-KO (61 % ± 20%); however, only a small fraction of progenitors and mature cells originated from Gfi1-KO HSCs (<1%). We therefore in summary propose that GFI1 has a dose-dependent role in the self-renewal and differentiation of HSCs.